KREATIVITAS DJOKO PRAKOSA DALAM KARYA TARI KRIDHA DWIPANGGA DI KABUPATEN SRAGEN - Pertiwi, Intan Hanny; Setyastuti, Budi (Institut Seni Indonesia Surakarta, 2023)
This research problem was formulated as a form of Kridha Dwipangga Dance performance which explains Djoko Prakosa's creative process. The results of this research show that the Kridha Dwipangga dance is a choreography and creativity of Djoko Prakosa with the theme of elephant fauna. Kridha Dwipangga Dance is intended as a form of education, tourism, and is expected to become an icon of Sragen Regency. The intended form of education is that the Kridha Dwipangga dance can be taught as learning material for Elementary School (SD) – Junior High School (SMP) levels. Apart from that, there is also education to introduce the Sangiran Archaeological Site to students. The form of tourism intended is related to the Circular Letter received by Sragen Regency from the Central Java Province Tourism and Culture Office so that each region can develop its tourism potential, including artistic and cultural potential. For this reason, Djoko Prakosa was asked to create a typical dance from Sragen Regency, hereinafter called the Kridha Dwipangga Dance. It is hoped that the iconic form of the Kridha Dwipangga dance will strengthen and publicize the Sangiran Archaeological Site which reveals many facts about well-known animal fossils, including elephants which are visualized in the form of dance. The Kridha Dwipangga dance icon presented by a group of female dancers inspired by the strong, protective and nurturing character of the elephant animal is a reflection of the Regent's attitude and responsibilities in running the government of Sragen Regency.